2021
DOI: 10.1016/j.jbc.2021.100874
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of STAC proteins: Calcium channel modulators and critical components of muscle excitation–contraction coupling

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 129 publications
0
22
0
Order By: Relevance
“…It is expressed almost exclusively in skeletal muscle. Along with other proteins, such as Cav1.1, RyR1, Cavβ1a, and junctophilin, STAC3 is responsible for the proper working of the skeletal muscle ECC machinery [ 8 ]. Nelson et al showed that STAC3-null mice, which are completely paralyzed, die at birth due to asphyxia [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expressed almost exclusively in skeletal muscle. Along with other proteins, such as Cav1.1, RyR1, Cavβ1a, and junctophilin, STAC3 is responsible for the proper working of the skeletal muscle ECC machinery [ 8 ]. Nelson et al showed that STAC3-null mice, which are completely paralyzed, die at birth due to asphyxia [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the amino acid substitution of the STAC3 protein Trp284Ser, Phe295Leu, and Lys329Asn affects the ECC by violating the interaction with the II–III loop of Cav1.1 [ 10 ]. All of these mutant isoforms reduce the affinity to Cav1.1 and disrupt the ECC calcium transients, while the isoform with the Trp284Ser substitution has the most negative effect on binding with Cav1.1 [ 8 ] and is associated with a more severe phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…SH3 and cysteine‐rich domain‐containing (STAC) proteins form a small group of adaptor proteins comprised of STAC1, STAC2, and STAC3. 1 , 2 While STAC1 and STAC2 are predominantly found in neuronal tissue, STAC3 is exclusively expressed in skeletal muscle. 3 In recent years, STAC3 has been touted as a potential “missing link” in skeletal muscle excitation‐contraction coupling (ECC), where it has been proposed to mediate the interactions between the voltage‐sensing dihydropyridine receptor (DHPR) and Ca 2+ ‐releasing ryanodine receptor 1 (RyR1).…”
Section: Introductionmentioning
confidence: 99%
“…SH3 and cysteine‐rich domain‐containing (STAC) proteins form a small group of adaptor proteins comprised of STAC1, STAC2, and STAC3 1,2 . While STAC1 and STAC2 are predominantly found in neuronal tissue, STAC3 is exclusively expressed in skeletal muscle 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This is referred to as depolarization-induced Ca 2+ release (DICR) 2,3 . Studies with knockout animals have revealed that functional and structural interactions between Cav1.1 and RyR1 in muscle require at least three additional components, a β1a auxiliary subunit of DHPR 4,5 , the Stac3 adaptor protein 6,7,8 , and junctophilins 9 , which may form specific machinery for DICR 4,5,10 .…”
Section: Introductionmentioning
confidence: 99%